Interaction of NANOS2 and NANOS3 with different components of the CNOT complex may contribute to the functional differences in mouse male germ cells - Suzuki, Atsushi (Biol Open, 2014)
NANOS2 and NANOS3 belong to the Nanos family of proteins that contain a conserved zinc finger domain, which consists of two consecutive CCHC-type zinc finger motifs, and contribute to germ cell development in mice. Previous studies indicate that there are redundant and distinct functions of these two proteins. NANOS2 rescues NANOS3 functions in the maintenance of primordial germ cells, whereas NANOS3 fails to replace NANOS2 functions in the male germ cell pathway. However, the lack of a conditional allele of Nanos3 has hampered delineation of each contribution of NANOS2 and NANOS3 to the male germ cell pathway. In addition, the molecular mechanism underlying the distinct functions of these proteins remains unexplored. Here, we report an unexpected observation of a transgenic mouse line expressing a NANOS2 variant harboring mutations in the zinc finger domain. Transcription of Nanos2 and Nanos3 was strongly compromised in the presence of this transgene, which resulted in the mimicking of the Nanos2/Nanos3 double-null condition in the male gonad. In these transgenic mice, P-bodies involved in RNA metabolism had disappeared and germ cell differentiation was more severely affected than that in Nanos2-null mice, indicating that NANOS3 partially substitutes for NANOS2 functions. In addition, similar to NANOS2, we found that NANOS3 associated with the CCR4-NOT deadenylation complex but via a direct interaction with CNOT8, unlike CNOT1 in the case of NANOS2. This alternate interaction might account for the molecular basis of the functional redundancy and differences in NANOS2 and NANOS3 functions.